2018
DOI: 10.1016/j.neuroscience.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

CRMP2–Neurofibromin Interface Drives NF1-related Pain

Abstract: An understudied symptom of the genetic disorder Neurofibromatosis type 1 (NF1) is chronic idiopathic pain. We used targeted editing of Nf1 in rats to provide direct evidence of a causal relationship between neurofibromin, the protein product of the Nf1 gene, and pain responses. Our study data identified a protein-interaction network with collapsin response meditator protein 2 (CRMP2) as a node and neurofibromin, syntaxin 1A, and the N-type voltage-gated calcium (CaV2.2) channel as interaction edges. Neurofibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…We conclude that CRMP2 regulation of NaV1.7 [9,10,12,13,22,28] is responsible for controlling DRG neurons excitability and that CRMP2 regulation of CaV2.2 is responsible for increased neurotransmitter release at the primary afferent [11,13,17,18]. For future therapeutic targeting, the specificity of action of CRMP2 toward CaV2.2 will reduce the potential for unwanted effects of novel CRMP2-targeted compounds.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We conclude that CRMP2 regulation of NaV1.7 [9,10,12,13,22,28] is responsible for controlling DRG neurons excitability and that CRMP2 regulation of CaV2.2 is responsible for increased neurotransmitter release at the primary afferent [11,13,17,18]. For future therapeutic targeting, the specificity of action of CRMP2 toward CaV2.2 will reduce the potential for unwanted effects of novel CRMP2-targeted compounds.…”
mentioning
confidence: 89%
“…In chronic pain, proteins regulating the N-type (CaV2.2) VGCCs can modulate nociception [1]. One such protein is the collapsin response mediator protein 2 (CRMP2) [3][4][5][6][7][8][9][10][11][12][13][14][15]. Our continuing studies have established CRMP2 as a bona fide binding partner and regulator of the presynaptic trafficking of CaV2.2 [4,8,13,[15][16][17][18].…”
mentioning
confidence: 99%
“…Moreover, some notable interactions between these proteins and other proteins of interest in the lab were missed by our bioinformatics approach. For example, NF1, a NMDA receptor-interacting protein (Husi et al, 2000) and Ras GTPase that regulates dendritic spines (Oliveira and Yasuda, 2014), interacts with and regulates the microtubuleregulating protein Crmp2 (Moutal et al, 2018), another Panx1-interacting identified by us, that itself regulates dendritic spines and NMDA receptor trafficking (Brustovetsky et al, 2014). Crmp2 also interacts with Crmp1, which was identified as a postsynaptic protein.…”
Section: Study Limitationsmentioning
confidence: 94%
“…Mouse paw incision and pSNL surgeries were done following published methods [13]. Allodynia was tested as described previously [3,14]. Data was analyzed as described by Chaplan et al [15] using the nonparametric method of Dixon.…”
Section: Surgeries and Behavioral Analysismentioning
confidence: 99%
“…Edonerpic maleate was found to disrupt CRMP2 tetramers [10]. Our previous body of work has established a role for phosphorylated and non-phosphorylated CRMP2 in control of voltage-gated calcium and sodium channels [1,[3][4][5][6][7][8][13][14][15][16][17][18][19][20][21][22]. Therefore, we tested the effect of edonerpic maleate on these channels.…”
mentioning
confidence: 99%